2004
DOI: 10.1210/jc.2003-032076
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Proliferative Retinopathy: A Cross-Sectional, Case-Control Study in 115 Patients with Type 2 Diabetes

Abstract: In this cross-sectional, case-control study we explored the association of proliferative diabetic retinopathy (PDR) with insulin resistance (IR) in type 2 diabetics with serum creatinine less than 2.0 mg/dl. For each PDR case, one reference case with background diabetic retinopathy (BDR) and two controls without retinopathy were identified. IR was evaluated by hyperinsulinemic euglycemic clamp; retinopathy was evaluated by indirect ophthalmoscopy and photography. Patients were matched by age, gender, and body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…11 Hadjadj et al 10 investigated the association between DR and insulin resistance score using a WHO recommendation 23 (that is, hypertension, personal history of lipid disorders, personal history of type 2 diabetes and obesity were considered). They found a significant association of DR with insulin resistance in type 1 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Hadjadj et al 10 investigated the association between DR and insulin resistance score using a WHO recommendation 23 (that is, hypertension, personal history of lipid disorders, personal history of type 2 diabetes and obesity were considered). They found a significant association of DR with insulin resistance in type 1 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant association of DR with insulin resistance in type 1 diabetic patients. Parvanova et al 11 have reported that proliferative retinopathy is associated with insulin resistance using a hyperinsulinemic-euglycemic clamp in 115 patients with type 2 diabetes mellitus. In this study, the DR was associated with BMI, triglyceride levels, HDL-C levels, fasting plasma glucose, fasting plasma insulin concentration and the HOMA index values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 GDR was calculated as the mean of the glucose infusion rate per kilogram of body weight required to maintain steady-state euglycemia during the last 30 minutes of a hyperinsulinemic-euglycemic clamp. 15 …”
Section: Bp Renal Function and Glucose Disposal Rate Evaluationsmentioning
confidence: 99%